2009
DOI: 10.1200/jco.2008.17.5026
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Quality of Life in Adult Survivors of Non-Hodgkin's Lymphoma

Abstract: The effort to promote physical activity among cancer survivors, who are at risk for poor quality of life as a result of treatment, is of great importance to the health of this growing population. As NHL, similar to other cancers, becomes a disease that people live with as opposed to one that people die as a result of, oncologists and primary care physicians will be increasingly challenged to provide evidence-based guidance for the long-term management of the patient's health. Consideration should be given to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
74
5
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 45 publications
8
74
5
7
Order By: Relevance
“…One prospective and three cross-sectional studies also observed clinically worse scores for HRQOL domains for NHL survivors compared with those of a normative population. 13,15,17,20 Numerous patients in our study showed large improvements (19-23%) or deteriorations (22-28%) within 1 year, which both indicate a clinically relevant change. 31 However, it is too soon to determine whether this can be defined as an actual change, due to regression to the mean.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…One prospective and three cross-sectional studies also observed clinically worse scores for HRQOL domains for NHL survivors compared with those of a normative population. 13,15,17,20 Numerous patients in our study showed large improvements (19-23%) or deteriorations (22-28%) within 1 year, which both indicate a clinically relevant change. 31 However, it is too soon to determine whether this can be defined as an actual change, due to regression to the mean.…”
mentioning
confidence: 82%
“…[8][9][10][11][12] In the last decades, more attention is being paid to HRQOL after cancer diagnosis. Some studies have investigated HRQOL and fatigue in NHL survivors, [13][14][15][16][17][18][19][20][21] but almost all used a cross-sectional approach (only one measurement at a defined time). 13,[17][18][19][20][21] However, the longitudinal course of fatigue and HRQOL in patients with NHL and their return to normal life remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This therapy, which was used in the last two decades for high-risk acute lymphoblastic leukemia (ALL) (typically at 18 Gy dose), is strongly associated with physical inactivity during adulthood. 9 Boys and girls (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years) who are long-term ALL survivors (41.5 years posttreatment) have significantly reduced cardiorespiratory fitness, and this reduction is correlated with cumulative chemotherapy dose. 7 Likewise, higher chemotherapy dose is associated with lower cardiac function.…”
Section: Introductionmentioning
confidence: 99%
“…The physical activity levels of adult hematological cancer survivors are indeed rather low and usually below the recommended levels. [13][14][15][16][17][18][19] Low physical activity levels impact a diverse set of outcomes, including fatigue 17 (though some controversy exists 20,21 ), sleep, 20 quality of life (QOL) 16,22 and risk of cardiovascular disease and hypothyroidism. 17 In ALL survivors, low physical activity levels begin during the first two decades of life.…”
Section: Introductionmentioning
confidence: 99%